Brexit, what Brexit? Euro area portfolio exposures to the United Kingdom since the Brexit referendum - Daniel Carvalho; Martin Schmitz (European Central Bank (ECB), 2022)
We study euro area investors' portfolio adjustment since the Brexit referendum in terms of securities issued in the UK or denominated in pound sterling, in the context of heightened policy uncertainty surrounding the exit process of the UK from the EU. Our sector-level analysis "looks-through" holdings of investment fund shares to gauge euro area sectors' full exposures to debt securities and listed shares. Our key finding is the absence of a negative "Brexit-effect" for euro area investors, which would have rendered UK-issued and pound-denominated securities generally less attractive. Instead, we observe that euro area investors increased their absolute and relative exposures to UK-issued and pound-denominated debt securities since the Brexit referendum. The analysis also reveals an increase in the euro area's exposure to listed shares issued by UK non-financial corporations, while the exposures to shares issued by UK banks declined. These findings should be seen against the backdrop of low yields on euro area debt securities and a strong recovery in UK share prices since the Brexit referendum, which appear to have largely outweighed the uncertainties associated with Brexit.
Keywords: F30; F41; G15; 330; Bilateral portfolio holdings; investment funds; cross-border investment; sovereign debt